عصرِ حاضر میں انسانی جان بچانے والے اداروں کے کردار کا قرآنی تعلیمات کی روشنی میں تجزیاتی مطالعہ: An Analytical Study of the Role of Life-Saving Institutions in the Contemporary Era in the Light of Qur’anic Teachings - Muhammad Akbar; Dr.Ghulam Haider (Al-Amīr Research Journal for Islamic Studies, 2025)
In contemporary society, life-saving institutions such as hospitals, ambulance services, rescue organizations (e.g., Rescue 1122), and NGOs play a crucial role in preserving human life. This research examines their services in light of Quranic teachings, emphasizing the sanctity of human life and the Islamic obligation to protect it. The study highlights key Quranic principles, including the value of saving lives (Al-Ma’idah 5:32), the importance of medical care, and the duty of communal cooperation in acts of righteousness (Al-Ma’idah 5:2). It also explores how modern healthcare aligns with prophetic traditions and Islamic ethics while addressing challenges like corruption and inequity in emergency medical services. The paper concludes that these institutions fulfill a sacred Islamic duty when operating with integrity, justice, and compassion, calling for enhanced ethical training to align their services with Quranic values. Keywords: Human life, Quranic teachings, Medical ethics, Rescue services, social responsibilities, Ethical challenges